2019
DOI: 10.1080/10511253.2019.1702219
|View full text |Cite
|
Sign up to set email alerts
|

Campus Criminal Victimization among Higher Education Students: A Diagnosis of Local Security in Porto

Abstract: This study addressed and characterized direct and indirect criminal victimization among college students and examined the associations between victimization and other variables. The participants were 775 students of both genders with a mean age of 21.76 years. Data were collected through self-reports using the "Diagnosis of Local Security Questionnaire". Overall, 8.6% of the students reported direct victimization, and 39.7% reported indirect victimization. The most reported crimes were robbery and theft, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…When we asked students to explain their answers, previous experience/observation was the main presented reason. Indeed, similarly to other international studies [ 15 , 46 , 47 ], in a previous work [ 10 ], we concluded that there was a significant association between perception of (in)security and victimization (both direct and indirect). It should be noted that a slightly higher percentage of students reported feelings of insecurity (26.6%) than those observed by Starkweather [ 12 ], namely 20.6%.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…When we asked students to explain their answers, previous experience/observation was the main presented reason. Indeed, similarly to other international studies [ 15 , 46 , 47 ], in a previous work [ 10 ], we concluded that there was a significant association between perception of (in)security and victimization (both direct and indirect). It should be noted that a slightly higher percentage of students reported feelings of insecurity (26.6%) than those observed by Starkweather [ 12 ], namely 20.6%.…”
Section: Discussionsupporting
confidence: 90%
“…Fear of crime and risk perception should be conceptually distinguished: namely, while the first consists of an emotional reaction toward the self or others, risk perception addresses a cognitive dimension. In a previous study [ 10 ], we found relevant results for objective insecurity: for instance, around 9% of the students were direct victims, and nearly 40% were indirect victims. Moreover, males presented a high risk for direct victimization, but there were no gender differences on indirect victimization.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations